Oral hygiene status and its association with oral hygiene practices among school going children of rural and urban areas in Kamrup district, Assam - Doley, Sulekha; Srivastava, Manvi (International Journal Of Community Medicine And Public Health, 2021)
Background: Oral hygiene, a state in which the surfaces of all the teeth are plaque free, is highly important in the promotion of oral health and also for good health in general. The aim of the present study was to assess the oral hygiene status among 13-14 years old school children in rural and urban areas in Kamrup Metropolitian (M) district, Assam. Methods: A total 1501 school children in the age group of 13-14 years were included in the study and oral hygiene status was assessed using oral hygiene index-simplified (OHI-S) given by Greene and Vermilion 1964. The children were asked to fill in the basic information in the proforma by themselves. The following statistical tests were used unpaired t test, Chi square test, one-way analysis of variance (ANOVA) test, post-hoc Bonferroni test to compare the oral hygiene status among the different age groups, gender and location. Results: The OHI-S values were found to be more among the males (2.72±1.50) as compared to the females (2.31±1.48) and the difference was highly significant (0.0001). The rural population and urban population constituted 50% of the total study sample each. Mean values of OHI-S index were more among rural children as compared to children residing in urban areas. The mean values showed that the p value was highly significant. Conclusions: Oral hygiene status was found to be poorer among rural school children compared to urban school children. Oral hygiene worsened as age advanced and found to be poorer in males than females.